Analysis of Capital Structure and Firm Value: The Moderating Role of Profitability in Manufacturing Companies - Yudha Pratama; Nur Aini (Economics Note, 2026)
Firm value reflects investors' perceptions of a company's future prospects and is an important indicator of corporate performance in capital markets. One of the financial decisions that may influence firm value is capital structure, as the proportion of debt and equity determines financing efficiency and financial risk. However, previous studies have reported inconsistent findings regarding the relationship between capital structure and firm value, suggesting that other factors may strengthen or weaken this relationship. Profitability is considered one of the key factors because highly profitable firms are generally more capable of utilizing debt effectively to generate greater returns and enhance shareholder wealth. This study aims to analyze the effect of capital structure on firm value and examine the moderating role of profitability in manufacturing companies listed on the Indonesia Stock Exchange (IDX). The study employed a quantitative approach using secondary data obtained from annual financial reports of manufacturing companies during the 2021–2024 period. A total of 60 companies meeting the purposive sampling criteria were selected, resulting in 240 firm-year observations. Capital structure was measured using the Debt-to-Equity Ratio (DER), firm value was proxied by the Price-to-Book Value (PBV), and profitability was measured using Return on Assets (ROA). Data were analyzed using descriptive statistics, classical assumption tests, and Moderated Regression Analysis (MRA) with IBM SPSS Statistics 27. The findings indicate that capital structure has a significant positive effect on firm value. Furthermore, profitability significantly strengthens the relationship between capital structure and firm value, indicating that companies with higher profitability are better able to optimize debt financing to create greater corporate value. These findings support the Trade-Off Theory and Signaling Theory, suggesting that an optimal capital structure combined with strong profitability enhances investor confidence and corporate market valuation. The study provides practical implications for corporate managers in determining financing strategies and emphasizes the importance of maintaining profitability to maximize firm value.